PENGARUH DISTRIBUSI REKAM MEDIS RAWAT JALAN TERHADAP WAKTU TUNGGU PELAYANAN DI POLIKLINIK VITREORETINA PUSAT MATA NASIONAL RUMAH SAKIT MATA CICENDO BANDUNG - Dina Sonia; Pipih Mulyadi (POLITEKNIK PIKSI GANESHA, 2019)
The purpose of this reseach is to know influence of distribution outpatient medical record to waiting times at Vitreoretina Clinic Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung. The reseach method used is quantitative reseach method with approach descriptive and for technical collection data used observation and library studies who has close relevance with at issue. Sampling technique used sample random sampling technique with sample 99 medical record. Base on reseach and Chi Square Tests there is influence significance with value 0,001. So the problem is (1) There is still waiting times Vitreoretina Clinic more than 60 minutes, (2) There is still inaccuracy times and distribution mistake medical record, (3) Has not yet Procedure Operational Standard (POS) about distribution medical record SMS gateway patient. Suggestion is (1) added clinic officers and nurse, (2) Do evaluation related mistakes in medical record distribution, (3) Prepare the new Procedure Operational Standard (POS) distribution of SMS gateway medical record.